Leaf Characteristics as Important Morphometric Discriminators for Chestnut (Castanea sativa Mill.) Genotypes - Grygorieva, Olga; Klymenko, Svitlana; Vinogradova, Yulia; Ilyinska, Antonina; Piórecki, Narcyz; Brindza, Ján (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
This study was carried out in order to determine the leaf characteristics of some chestnut (Castanea sativa Mill.) genotypes in the M.M. Gryshko National Botanical Garden (Kyiv, Ukraine) and also to determine whether the leaf morphometric characteristics could be used for differentiation of genotypes. In this study, 9 chestnut genotypes (CS-01 – CS-09) were used. Some leaf parameters such as lamina length, lamina width, petiole length, petiole width, petiole thickness, teeth length, teeth width, stomata length, stomata width were studied. Morphometric parameters were following: leaves length from 85.0 to 250.0 mm, leaves width from 26.0 to 100.0 mm, petiole length from 8.07 to 36.18 mm, petiole width from 0.91 to 2.60 mm, petiole thickness from 0.81 to 2.44 mm, teeth length from 1.27 to 5.05 mm, teeth width 0.87 to 2.82 mm. The shape indexes of leaves were found ranging from 2.45 to 4.26. Analysis of coefficient of variation (CV) showed a high variability in morphometric characteristics between Castanea sativa samples. Data showed that the teeth width is the most variable signs (from 15.30 to 22.18 %). Other studied characteristics have an average level of variability. Collected quantitative data were subjected to principal hierarchical cluster analysis. The cluster analysis of morphometric parameters exhibited that broad morphologic diversity was found in Castanea sativa genotypes examined in this study. Most of the chestnut genotypes could be differentiated easily by using leaf morphometric characteristics.